Influence of Ionic Liquid Structure on Supported Ionic Liquid Membranes Effectiveness in Carbon Dioxide/Methane Separation - Iwona Cichowska-Kopczyńska; Monika Joskowska; Bartosz Dębski; Justyna Łuczak; Robert Aranowski (Journal of Chemistry)
This paper indicates the possibility of application of imidazolium ionic liquids immobilized in polymeric supports—supported ionic liquid membranes—in CO2 separation from gaseous streams (e.g., biogas). Imidazolium salts containing alkyl fluoride anions, bis(trifluoromethylsulfonyl)imide and trifluoromethanesulfonate, selectively separating CO2 were used. The permeability of CO2 through membranes was investigated under gas pressure of 30 kPa and temperature range 283–298 K. Permeability values occurred to be higher for ionic liquids containing bis(trifluoromethylsulfonyl)imide anion. Moreover, CO2 permeability exhibited an increase with increasing temperature for all investigated systems. Stability of supported ionic liquid membranes was studied. In total, polypropylene membrane revealed the best properties, mechanical stability and observed wettability of this support were better than for polyamide and polyvinylidene fluoride ones. Polyethersulfone supports showed similar contact angles; however, its mechanical stability was significantly lower. Obtained results allowed to evaluate the effectiveness of separation process using selected ILs and supports.